Exploring the Role of Fathers in the Qur'an for Management Curriculum Based on Qur'anic Values at Islamic Elementary School - Muhammad Imam Najmudin; Muhammad Chirzhin; Azam Syukur Rahmatullah; Fitriah M. Suud (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to investigate the role of the father in the management curriculum, grounded in the values of the Qur’an, at Amanah Ummah Islamic Elementary School, Surakarta. Focus on the main study. This is the father’s contribution to implementing the core values of Islamic education, such as monotheism, morals, wisdom, and tarbiyah, which form the foundation for the development of character in students. The method used is a qualitative descriptive study, with data collection techniques including in-depth interviews, participatory observation, and documentation. The results of the study show that fathers’ participation is still classified as low and not yet well organized, especially in supporting continuity education between school and home. Some factors affecting matter, among other things, are busy work, limited knowledge of literacy in Islam, and the lack of an existing system for effective communication between teachers and guardians, especially fathers. Research recommends strengthening collaboration between schools and families through fathers’ forums, parenting training grounded in the values of the Qur’an, and the development of an integrated monitoring system to support and optimize the role of fathers as strategic partners in school management of the curriculum. Implications from the study. This emphasizes the importance of integrating the role of parents into planning and implementing the curriculum as part of comprehensive, value-oriented Islamic education.